Mediterranean diet research trajectories in China (2006–2025): a scoping review and scientometric analysis to localize global nutrition models - Jia, Dongming; Xue, Shengxia (Frontiers in Nutrition, 2025)
BackgroundMediterranean-diet (MedDiet) principles are increasingly invoked to counter China’s nutrition-transition-driven epidemic of cardiometabolic disease, yet no field-wide synthesis of this scholarship exists. A bibliometric assessment can expose thematic evolution, knowledge gaps and localization pathways.MethodsWe systematically searched Web of Science Core Collection and CNKI for Chinese-affiliated MedDiet human-health articles published between 2006 and 2 February 2025. After PRISMA-ScR screening we retained 384 records. VOSviewer and COOC mapped co-authorship, citations and keywords; latent-Dirichlet allocation detected topic drift; compound annual growth rate (CAGR) and field-weighted citation impact (FWCI) indexed performance. All data and scripts are openly archived.ResultsAnnual output climbed from one article in 2006 to 76 in 2022 (CAGR = 23%); FWCI = 1.34. Seven keyword clusters now pivot on gut-microbiome science, digital adherence and sustainability rather than early cardiometabolic replication. Temporal segmentation revealed three phases: replication (2006–2013), public-health expansion (2014–2019) and cross-disciplinary innovation (2020–2025). Bibliographic coupling resolved five citation schools; Jiangnan-diet localization has migrated into the leading clinical cluster. Lexical drift highlights ingredient substitution (rapeseed-oil phenolics) and late adoption of carbon-footprint terminology.ConclusionChinese MedDiet scholarship is recalibrating toward a culturally adapted, digitally enabled and climate-aligned paradigm. Longer m-health-supported trials, life-course epidemiology and multi-omics Jiangnan cohorts are warranted to translate current bibliometric momentum into population-level health and sustainability gains.